Synthesis, characterization and analytical studies of two new shighff bases (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Schiff bases, 4-((4-(dimethylamino) benzylidene) amino) benzenesulfonamide (Sb1) and 4-((2-hydroxybenzylidene) amino) benzenesulfonamide (Sb2) were synthesised. and then characterized using FTIR, UV-visible, 1HNMR and mass spectrum. Analytical studies were showed that the best solubility of (Sb1) and (Sb2) were in DMSO and ethanol respectively. Though, the suitable pH values of (Sb1) and (Sb2) were found to be in the pH12, and three isopiestic points were gained in the spectrum of each base. The protonation constants pKb of nitrogen atom and the ionization constants pKa of SO2- group and OH-group were attended for (Sb1) and (Sb2) respectively. These results indicated the suggested ionization scheme in acidic and basic media for each base. Further, the (Sb1) and (Sb2). Further, the biological activity of each base was tested against three different bacteria, (Staphylococcus Aureus, Escherichia Coli and Pseudomonas Aeruginosa). The results showed that each of (Sb1) and (Sb2) was shows reasonable activity against Escherichia Coli. But, the (Sb1) did not have any affect towered Staphylococcus Aureus and Pseudomonas Aeruginosa in contrast with (Sb2), which was showed similarity in its activity toward Staphylococcus Aureus and Pseudomonas Aeruginosa.